The Impact of Paratuberculosis on Milk Production, Fertility, and Culling in Large Commercial Hungarian Dairy Herds - Ozsvari, Laszlo; Harnos, Andrea; Lang, Zsolt; Monostori, Attila; Strain, Sam; Fodor, Istvan (Frontiers in Veterinary Science, 2020)
Paratuberculosis (PTBC) is a chronic disease caused by Mycobacterium avium subsp. paratuberculosis (MAP), which is common in dairy herds worldwide, although the scale of its impact on herd productivity is unclear. The aim of our study was to determine the differences between MAP ELISA positive vs. negative cows in terms of milk production and quality, reproductive parameters, and culling. The data of five large dairy herds that participated in the voluntary PTBC testing program in Hungary were analyzed. Cows were tested by ELISA (IDEXX Paratuberculosis Screening Ab Test, IDEXX Laboratories, Inc., Westbrook, ME, USA) using milk samples collected during official performance testing. The outcome of the initial screening test involving all milking cows in the herds was used for the classification of the cows. The 305-day milk production, reproduction and culling data of 4,341 dairy cows, and their monthly performance testing results (n=87,818) were analyzed. Multivariate linear and logistic models, and right censored tobit model were used for the statistical analysis. Test-day and 305-day milk production of ELISA positive cows decreased by 4.6 kg [95% CI: 3.5-5.6 kg, p<0.0001, (-13.2%)] and 1,030 kg [95% CI: 708-1,352 kg, p<0.0001, (-9.4%)], compared to their ELISA negative herdmates, respectively. Milk ELISA positive cows had 35.8% higher [95% CI: 17.9-56.4%, p<0.0001] somatic cell count, on average. Test positive cows conceived 23.2 days later [95% CI: 9.2-37.3 days, p=0.0012, (+16.5%)] and their calving interval was 33.8 days longer [95% CI: 13.2-54.4 days, p=0.0013, (+9.7%)], compared to the negative cows, on average. Milk ELISA positive cows were less likely to conceive to first insemination (odds ratio: 0.49, 95% CI: 0.31-0.75, p=0.0013), and required 0.42 more inseminations to conceive [95% CI: 0.07-0.77, p=0.0192, (+13.7%)], on average. Milk ELISA positive cows were culled 160.5 days earlier after testing compared to their ELISA negative herdmates (95% CI: 117.5-203.5 days, p<0.0001). Our results suggest that MAP ELISA positive cows experience decreased milk production, milk quality, fertility, and longevity, which supports the need to control the prevalence of paratuberculosis in dairy herds.